2022
DOI: 10.1038/s41467-022-28974-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered intracellular domains control key features of the mechanically-gated ion channel PIEZO2

Abstract: A central question in mechanobiology is how mechanical forces acting in or on cells are transmitted to mechanically-gated PIEZO channels that convert these forces into biochemical signals. Here we examined the role of the intracellular domains of PIEZO2, which account for 25% of the channel, and demonstrate that these domains fine-tune properties such as poking and stretch-sensitivity, velocity coding and single channel conductance. Moreover, we show that the intrinsically disordered linker between the transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 66 publications
10
57
0
Order By: Relevance
“…Lastly, Piezo2 inhibits neurite outgrowth in N2a cells 16 . In addition to membrane curvature, specific Piezo regions and Ca 2+ signaling induced by the activation of Piezo can also play important roles in regulating filopodia formation and growth 16,41,42 . Further studies are required to fully dissect the contribution of each of these variables.…”
Section: Piezo1 Inhibits Filopodia Formationmentioning
confidence: 95%
See 1 more Smart Citation
“…Lastly, Piezo2 inhibits neurite outgrowth in N2a cells 16 . In addition to membrane curvature, specific Piezo regions and Ca 2+ signaling induced by the activation of Piezo can also play important roles in regulating filopodia formation and growth 16,41,42 . Further studies are required to fully dissect the contribution of each of these variables.…”
Section: Piezo1 Inhibits Filopodia Formationmentioning
confidence: 95%
“…Secondly, Piezo1 negatively regulates the morphological activity (i.e., number of protrusions) of muscle stem cells 42 . Lastly, Piezo2 inhibits neurite outgrowth in N2a cells 16 . In addition to membrane curvature, specific Piezo regions and Ca 2+ signaling induced by the activation of Piezo can also play important roles in regulating filopodia formation and growth 16,41,42 .…”
Section: Piezo1 Inhibits Filopodia Formationmentioning
confidence: 95%
“…In contrast, PIEZO2 is intriguingly known for a preferential response to indentation of the cell membrane, whereas PIEZO1 is sensitive to all forms of mechanical deformation ( Ikeda and Gu, 2014 ; Moroni et al, 2018 ; Shin et al, 2019 ). A battery of data has indicated PIEZO2 is less sensitive to membrane stretch ( Coste et al, 2015 ; Moroni et al, 2018 ; Verkest et al, 2022 ). Shin et al (2019) showed that positive pressures under the cell-attached mode could activate PIEZO2 currents in a Merkel cell line and PIEZO2-overexpressed HEK 293T cells, but negative pressure failed to activate PIEZO2 in these cells, which suggests that not all kinds of membrane stretching can induce PIEZO2 gating.…”
Section: Force From Filament the Tether Model Of Mechanosensitive Ion...mentioning
confidence: 99%
“…The PIEZO2-PIEZO1 beam chimera lost much of its sensitivity to latrunculin A. Verkest et al (2022) reported that an intrinsically disordered domain 5 (IDR5) in the PIEZO2 molecule was required for the interaction between PIEZO2 and the actin cytoskeleton. Deletion of IDR5 specifically reduced membrane indentation-evoked PIEZO2 currents, but showed no effects on negative pressure-evoked PIEZO2 currents.…”
Section: The Role Of the Cytoskeleton In The Mechanogating Of Mechano...mentioning
confidence: 99%
See 1 more Smart Citation